The influence of systemic racism on quarter-life crisis in The Autobiography of Malcolm X (as told to Alex Haley) - Bhakti Satrio Nugroho; Dwi Septi Aryani (EduLite: Journal of English Education, Literature and Culture, 2021)
This paper aims to analyze the influence of systemic racism on quarter-life crisis, experienced by Malcolm X, as seen in The Autobiography of Malcolm X (As Told to Alex Haley). Its emphasis is to find the relation between racial segregation in American society and its influence on quarter-life crisis, which is a psychological crisis of uncertainty, self-insecurity and identity confusion, occurs during emerging adulthood. Therefore, by applying a qualitative method, this research is under Post-Nationalist American Studies and psychosocial approach as an integrated paradigm which accommodates the inter-disciplinary aspects of “self and society”. The analysis showed that racial segregation, in the field of education and job occupation, is a form of systemic racism which influences Malcolm X’s mental wellness as an emerging adult African-American. He experiences Robinson’s phases of quarter-life crisis which are locked in, separation/time-out, exploration and rebuilding. In fact, racial segregation in this narrative works as “a function of blocked opportunities” which disallows young African-Americans to develop their own competencies and to achieve their “American Dream’. However, in the development of his quarter-life crisis, Malcolm X managed to rebuild his new long-term commitment contributing to the reconstruction of his adult identity as an African-American Muslim activist.